Learning and teaching by using task videos activities with university students of ELE in the field of Architecture and Construction - Úbeda Mansilla, Paloma; Escribano Ortega, Maria Luisa (Didáctica. Lengua y Literatura, 2019)
This article presents a research experience in the field of the Spanish Academic course for Architecture and Construction, aimed at foreign students at the School of Architecture of the Universidad Politécnica de Madrid. The participating students presented a linguistic profile of Independent User, and between B1 and B2 average levels, according to criteria established in the Common European Framework of Reference for Languages: learning, teaching and evaluation (CEFR) gathered by the European Portfolio of Academic Languages and Professional (ACPEL). The students created, designed and recorded situations of their daily academic environment, learning specific vocabulary and grammatical structures in natural contexts for them, within a discourse of their specialty. The proposal was valued positively by the students; the videos produced serve as a reference for their own feedback and as a learning tool to encourage other international students.
Keywords: Spanish for specific purposes; Orality; Learning activities; Audiovisual media; International Students; Architecture